Evaluasi Tingkat Kesiapan Pemerintah Kota Batu Dalam Menerapkan Pemerintahan Berbasis Elektronik (E-Government) Dengan Menggunakan ICT Readiness - Ratna Dwi Anjani; Suprapto Suprapto; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Advances in the development of e-government systems in Indonesia is the result of Instruction of the President of the Republic of Indonesia Number 3 in 2003. One of the agencies implementing e-government is the Government of Batu City. As one of the governments that will implement several electronic systems to support services, the Government of Batu City needs to evaluate the level of readiness in implementing e-government. This research uses model of ICT Readiness Assessment. The model focuses on ICT infrastructure factors, organizations, ICT availability and security and the legal environment. This research takes objects from seven Struktur Perangkat Daerah (SOPD) namely Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappelitbangda), Badan Keuangan Daerah (BKD), Bagian Administrasi Perekonomian dan Pembangunan (Ekbang), Bagian Pelayanan Pengadaan (ULP), Inspektorat, Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) dan Dinas Komunikasi dan Informatika (Kominfo). The research methodology used is qualitative by collecting data using interviews, questionnaires, and observations. The results of the analysis shows that the readiness to implement e-government in the seven SOPDs, BKD, Dinas kominfo and BKPSDM are at level 3, while Bappelitbangda, Ekbang, Inspektorat, and ULP are at level 2. From the result of research then prepared to improve e-government implementation readiness.